Prion propagation and inositol polyphosphates - Wickner, Reed B. (Curr Genet, 2017)
The [PSI+] prion is a folded in-register parallel β-sheet amyloid (filamentous polymer) of Sup35p, a subunit of the translation termination factor. Our searches for anti-prion systems led to our finding that certain soluble inositol polyphosphates (IPs) are important for the propagation of the [PSI+] prion. The IPs affect a wide range of processes, including mRNA export, telomere length, phosphate and polyphosphate metabolism, energy regulation, transcription and translation. We found that 5-diphosphoinositol tetra(or penta)kisphosphate or inositol hexakisphosphate could support [PSI+] prion propagation, and 1-diphosphoinositol pentakisphosphate appears to inhibit the process.